2022
DOI: 10.3390/app12031679
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Convolutional Neural Network on Multi-Temporal Synthetic Aperture Radar Images for Urban Flood Potential Mapping in Jakarta

Abstract: Flooding in urban areas is counted as a significant disaster that must be correctly mitigated due to the huge amount of affected people, material losses, hampered economic activity, and flood-related diseases. One of the technologies available for disaster mitigation and prevention is satellites providing image data on previously flooded areas. In most cases, floods occur in conjunction with heavy rain. Thus, from a satellite’s optical sensor, the flood area is mostly covered with clouds which indicates ineffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…Perubahan iklim yang terjadi membuat meningkatnya frekuensi kejadian bencana alam di Indonesia diantaranya banjir (Klipper et al, 2021). Selain bencana lonsor banjir adalah bencana alam yang merugikan, terutama di daerah perkotaan seperti Ambon, karena berdampak pada sejumlah besar penduduk seperti kerugian material akibat kerusakan harta benda akibat genangan banjir (Riyanto et al, 2022) . Banjir adalah bencana alam yang terjadi hampir setiap tahun terutama pada wilayah perkotaan (Amira et al, 2020).…”
Section: Pendahuluanunclassified
“…Perubahan iklim yang terjadi membuat meningkatnya frekuensi kejadian bencana alam di Indonesia diantaranya banjir (Klipper et al, 2021). Selain bencana lonsor banjir adalah bencana alam yang merugikan, terutama di daerah perkotaan seperti Ambon, karena berdampak pada sejumlah besar penduduk seperti kerugian material akibat kerusakan harta benda akibat genangan banjir (Riyanto et al, 2022) . Banjir adalah bencana alam yang terjadi hampir setiap tahun terutama pada wilayah perkotaan (Amira et al, 2020).…”
Section: Pendahuluanunclassified
“…The results showed that areas with low resilience tended to have high multi-disaster hazards. Figure 4 shows that inundation occurs in residential areas due to prolonged rains, while the rivers cannot accommodate the overflowing water (Riyanto, Rizkinia, Arief, & Sudiana, 2022;Shige-Eda, Akiyama, Duran, Kanaya, & Katsura, 2022). The puddle's dark brown color indicates that the upstream area's erosion process is intensive, so various forms of prevention, such as reforestation or the construction and checking dams, need to be carried out as soon as possible (Dunn & Minderhoud, 2022;Singh et al, 2022;Y.…”
Section: Land Resilience Towards the Disaster Hazard In Kendarimentioning
confidence: 99%
“…The Deep Neural Network (DNN) in combination with spatial analysis can provide a strong technique for evaluating the geographical data to identify the susceptible regions more rapidly (Riyanto et al 2022). GIS has also been applied to investigate floods, and their severe damage (Wang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It can also be applied to integrate different targets to process the given data in complex ways (Nayak et al 2022). The coupled DNN and GIS have been widely applied in flood susceptibility assessment and modeling (Riyanto et al 2022). Various studies have confirmed that such hybridization can be applied to detect flood susceptibility regions where the technologies applying artificial intelligence in combination with spatial analysis seek to classify and process the geospatial data in a way that goes beyond simple input/output protocols.…”
Section: Introductionmentioning
confidence: 99%